Neuroprotective action of hordenine against the Aluminium Chloride (AlCl3) induced Alzheimer's diseases & associated memory impairment in experimental rats - Mohit Agrawal; Manmohan Singhal; Bhupesh Chander Semwal; Swamita Arora; Bhoopendra Singh; Vandana Sikarwar; Pranshul Sethi; Hema Chaudhary; Wasim Akram; Samir Bhargva; Bhavna Kumar; Sunam Saha; et al. (Elsevier, 2024)
Objective: To investigate the neuroprotective action of hordenine against the cognitive dysfunction induced by aluminium chloride (AlCl3) in Wistar rats Methodology: Rats were given oral doses of hordenine (25 and 50 mg/kg), donepezil (5 mg/kg), and AlCl3 (175 mg/kg) for 28 days. During the study, neurobehavioral parameters included Morris water maze (MWM), open field test (OFT), and novel object recognition test (NORT) to assess the cognitive effect. On the 29th day rats were sacrificed and brain tissues removed for biochemical and histopathological analyses. Results: AlCl3 rats exhibited altered neurobehavioral patterns and cognitive impairment in experimental rats. Although AlCl3 raised the levels of mid-brain acetylcholinesterase (AChE), lipid peroxidation (LPO), nitrite, tumour necrosis factor-α (TNF-α), interleukin-β (IL-β), nuclear factor-kappa B (NF-κB), brain-derived neurotrophic factor (BDNF), and it decreased the levels of antioxidants including glutathione (GSH), catalase, superoxide dismutase (SOD), and body weight. In cortical and hippocampal slices, AlCl3 also revealed anatomical alterations that resulted in a decrease in the density of microglia. But donepezil and hordenine reversed these alterations to normal while demonstrating a neuroprotective effect against AD which is caused by AlCl3. Conclusion: Hordenine improved memory and other cognitive functions, demonstrating a neuroprotective effect against AlCl3-induced Alzheimer's disease. These findings imply that hordenine may be able to reverse the effects of oxidative stress and neuroinflammation, improve cognitive decline, and protect the brain's histological structure.